Synthesis and Characterization of Novel Phthalimide‐pyrano[3, 2‐c]chromene and Phthalimide‐pyrano‐2‐one Hybrids. (29th May 2018) - Sameem, Bilqees; Saeedi, Mina; Mahdavi, Mohammad; Nadri, Hamid; Vafadarnejad, Fahimeh; Amini, Mohsen
Abstract : Coumarin skelton holds substantial promise for further exploration because of its immense pharmacological potential. In this pursuit, a series of phthalimide‐chromen and phthalimide‐pyran‐2‐one hybrids were synthesized in efficient yields via one‐pot multicomponent reaction of aldehyde linked to phthalimide moiety, 4‐hydroxy coumarin/4‐hydroxy‐6‐methyl‐2H‐pyran‐2‐one, and malanonitrile by Knoevenagel reaction at room temperature in the presence of DABCO as catalyst. The compounds were characterized by 1 H NMR and 13 C NMR, MS, and FTIR. All the compounds consisting of phthalimide‐chromen/pyrano‐2‐one moieties tethered by spacers of varying lengths were evaluated for their biological activity in Ellman's assay. Most of the compounds feebly inhibited Acetylcholinesterase Enzyme and were inactive toward Butyrylcholinesterase Enzyme. Abstract :